Losing your edge: climate change and the conservation value of range‐edge populations. Issue 19 (14th September 2015) - Rehm, Evan M.; Olivas, Paulo; Stroud, James; Feeley, Kenneth J.
Abstract Populations occurring at species' range edges can be locally adapted to unique environmental conditions. From a species' perspective, range‐edge environments generally have higher severity and frequency of extreme climatic events relative to the range core. Under future climates, extreme climatic events are predicted to become increasingly important in defining species' distributions. Therefore, range‐edge genotypes that are better adapted to extreme climates relative to core populations may be essential to species' persistence during periods of rapid climate change. We use relatively simple conceptual models to highlight the importance of locally adapted range‐edge populations (leading and trailing edges) for determining the ability of species to persist under future climates. Using trees as an example, we show how locally adapted populations at species' range edges may expand under future climate change and become more common relative to range‐core populations. We also highlight how large‐scale habitat destruction occurring in some geographic areas where many species range edge converge, such as biome boundaries and ecotones (e.g., the arc of deforestation along the rainforest‐cerrado ecotone in the southern Amazonia), can have major implications for global biodiversity. As climate changes, range‐edge populations will play key roles in helping species to maintain or expand their geographic distributions. The loss of these locally adapted range‐edge populations through anthropogenic disturbance is therefore hypothesized to reduce the ability of species to persist in the face of rapid future climate change.